Evaluasi dan Perbaikan Proses Bisnis menggunakan Metode Business Process Improvement (BPI) (Studi Kasus pada Proses Produksi PT. Kencana Tiara Gemilang (KTG)) - Dinda Aulia Rachmanda; Yusi Tyroni Mursityo; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT. Kencana Tiara Gemilang is a manufacturing company based on plastic sector and located in Singosari, Malang. PT. Kencana Tiara Gemilang products are geosynthetic, agricultural and innovation products. Problems that often occur in the production process are sales & marketing take a long time to receive some orders, PPIC makes the wrong calculations in determining raw materials, and the production process takes a long time because of Human Resources (HR). For this reason, it is necessary to evaluate the production process. After conducting interviews and observations, it can be seen that the production process is divided into three business processes, such as the production planning process, the production process, and the product evaluation process. The three business processes will be modeled by using the Business Process Model and Nation (BPMN) with a bizagi modeler as a tool. Furthermore, evaluation and analysis were carried out using the Failure Mode and Effect Analysis (FMEA) method to get the priority of the existing problems based on the RPN value. After that, the next step is to make recommendations for business process improvements using the Business Process Improvement (BPI) method with streaming tools. Finally, compare the results of the current business process simulation (AS-IS) and recommendations (TO-BE). The simulation comparison results show that there is a savings in the production planning business process of 21.55 % for Max Time and 5.01 % for Average Time, the production business process is 18.36 % for Max Time and 16.38 % for Average Time, and The product evaluation business process is 32.06 for Max Time and 42.48 % for average time. Savings indicates that the duration of time has decreased from the current ongoing business process (AS-IS) into a business process recommendation (TO-BE).